A biphasic model for full cycle simulation of the human heart aimed at rheumatic heart disease. (May 2020) - Hopkins, Gary; Skatulla, S.; Moj, L.; Ricken, T.; Ntusi, N.; Meintjes, E.
Highlights: Porous media theory is coupled with active cardiac contraction and circulatory haemodynamics. Porous media theory is used to simulate the behaviour of a human heart affected by rheumatic heart disease, including the effects of blood within the cardiac tissue which has previously been neglected. It is shown that growth and remodelling of the patient's rheumatic heart could have caused (i) a decreased stroke volume and higher cavity pressure, (ii) increased fibre stress and strain and (iv) increased sarcomere length and active tension response. Abstract: Rheumatic heart disease (RHD) is identified as a serious health concern in developing countries, specifically amongst young individuals, accounting for between 250 000 and 1.4 million deaths annually. As such, attention is initially placed on the importance of the development of a cardiac analysis toolbox with functionality for pathophysiological analysis of the disease. Subsequently, in order to develop a toolbox to further the understanding of the mechanisms of the disease as linked to changes in the cytoskeletal architecture and hypertrophy of cardiac myocytes, a continuum bi-phasic model applicable to cardiac tissue is formulated based on the theory of porous media (TPM). This makes it possible to account for interactions and contributions of multiple phases of constituent materials as well as concentrations of solved components, which in computational cardiac modelling are the solid phase – the cardiac tissue – and the liquid phase – blood and interstitial fluid. Therefore, subsequent attention is paid to the cardiac model development in order to implement a sound base on which to add strain- and nutrient-driven phase transition, in addition to a nutrient phase contained within the liquid phase. To this end, based on thermodynamical restrictions, constitutive relations are proposed for stress, permeability, seepage velocity and interaction forces. The approach is implemented in the in-house computational cardiac mechanics toolbox SESKA which supports finite element as well as Element-free Galerkin -based approximations. This paper considers the passive and active non-linear elastic material behaviour of the myocardium of the left ventricle coupled with porous media theory, along with an additional coupling to the haemodynamics of the circulatory system, facilitating modelling of the full cardiac cycle. In order to illustrate the potential and efficacy of the approach with qualitative results, a human heart affected by RHD is investigated, making use of cardiovascular magnetic resonance scans taken over a period of two years to generate realistic 3D computer models.